Editorial - Robles Olivos, Rafael (2022)
Society and its multiple faces seem to be going through, for some time now, a few decades, an increasingly changing, and sometimes unpredictable future, in a framework where technology marks and defines the beat of the times.The challenges and opportunities that cyberspace poses to different areas of human development, the ups and downs and warnings in the most unstabledemocracies, as well as the appearance of leaders with messianic airs, backed by millions of followers (in the streets and social networks), make up a scenario to which it is necessary take the pulse continuously, to understand where we are, where we have come from come and what are the potential ways forward.